Gynecologic Cancer InterGroup (GCIG) Consensus Review for Squamous Cell Carcinoma of the Ovary. (1st November 2014) - Glasspool, Rosalind M.; Martín, Antonio González; Millan, David; Lorusso, Domenica; Åvall-Lundqvist, Elisabeth; Hurteau, Jean A.; Davis, Alison; Hilpert, Felix; Kim, Jae-Weon; Alexandre, Jérôme; Ledermann, Jonathan A.
Abstract : Abstract: Squamous cell carcinoma of the ovary is a rare complication of mature cystic teratoma. The epidemiology, pathology, diagnosis, and management of this rare tumor are reviewed. Clinical characteristics, preoperative imaging, and tumor markers may help to predict malignancy preoperatively. Complete cytoreduction should be the aim of surgery. The prognosis for stage 1A disease is good, but for women with advanced or recurrent disease, it is very poor and has not improved in recent years. At present, there are insufficient data to provide clear guidance on the optimal management strategy for advanced disease, and there is a need to gain an understanding of the biology and to develop novel effective therapies. This will require coordinated international collaboration.